Knowledge, attitude and practice of women about control actions for cancer breast - Marinna Maria de Andrade Costa (2016)
Breast cancer is the type of cancer that affects more women worldwide, accounting for 22% of new cases each year. The nurse takes vital role in breast cancer control actions. But the success of breast cancer control program is directly dependent on, among other factors, the participation of users, since they must attend gynecological consultations, conduct examinations, participate in educational activities and put into practice the knowledge acquired. Given the importance of strategies to reduce mortality from breast cancer and the role of women seen in primary care, the study aimed to assess the knowledge, attitude and practice of women about control actions for cancer breast. Treat It will be an evaluative study, cross-sectional survey using the Knowledge, Attitude and Practice (KAP). The study was developed in the city of Fortaleza-CE. hey were listed 43 units of Primary Health Care distributed among the six Regional Executive Secretariats. The users that are accompanied by the ESF and that are in the age of risk for incidence of breast cancer (> 20 years), according to the Ministry of Health, composed the sample, totaling 387 women. Data will be collected with from an interview using two instruments: the questionnaire adapted from Oliveira (2014) and the questionnaire that corresponds to the Economic Classification Criteria of Brazil Brazilian Association of Research Companies (ABEP).The data will be analyzed based on analytical statistics and presented in tables and charts with absolute and relative frequencies. The results showed us that 368 women (94.8%) had adequate knowledge, but 214 (55.1%) had inadequate and attitude 279 (71.9%) inadequate practice in relation to early detection methods of breast cancer. These factors were influenced by age and Executive Secretary Regional (SER) in which women lived. This knowledge about the characteristics of the population, identifying gaps in knowledge, difficulties in adhering to exams and the cultural behavior of women subsidizes the actions of health professionals, guiding them in the development of techniques and strategies for population mobilization for adoption and maintaining a healthy behavior that direct self-care and health promotion.